2021
DOI: 10.1155/2021/5594733
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Detection of Obstructive Sleep Apnea Events Using a Deep CNN‐LSTM Model

Abstract: Obstructive sleep apnea (OSA) is a common sleep-related respiratory disorder. Around the world, more and more people are suffering from OSA. Because of the limitation of monitor equipment, many people with OSA remain undetected. Therefore, we propose a sleep-monitoring model based on single-channel electrocardiogram using a convolutional neural network (CNN), which can be used in portable OSA monitor devices. To learn different scale features, the first convolution layer comprises three types of filters. The l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…Single-channel ECG lead signals are acquired and analyzed using CNN-LSTM network. The Kappa coefficient value of CNN was 0.89, to that of CNN-LSTM network was 0.92 [ 112 ].…”
Section: Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Single-channel ECG lead signals are acquired and analyzed using CNN-LSTM network. The Kappa coefficient value of CNN was 0.89, to that of CNN-LSTM network was 0.92 [ 112 ].…”
Section: Classificationmentioning
confidence: 99%
“…The apnea and the normal signals are identified efficiently by CNN-LSTM network. The score transitions between each epoch are considered as a hideous process [ 112 ].…”
Section: Inferences From the Surveymentioning
confidence: 99%
“…Then, stacked autoencoder-based deep neural network (SAE-DNN) and support vector machine (SVM) are used to categorize apneic and normal segments. Zhang et al [ 11 ] suggested a sleep monitoring model based on a single-channel electrocardiogram using a convolutional neural network (CNN). Rajesh et al [ 9 ] extracted moments of power spectrum density, waveform complexity measures, and higher-order moments from the 1 min segmented ECG subbands obtained from discrete wavelet transform (DWT).…”
Section: Introductionmentioning
confidence: 99%
“…So, developing methods that can accurately detect apnea with a few signals at home is critical. ese approaches were focused on biosignals such as respiratory, snoring, SpO2, and ECG signals, and several authors have achieved a high level of performance in terms of OSA detection [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation